Tinjauan Rancangan Undang-Undang Keamanan Nasional Indonesia Dalam Perspektif Menghadapi Ancaman Masa Depan (pp. 155-180) - Wempy Pasaribu; M. Mossadeq Bahri; Margaretha Hanita; Hanief Ghafur (Universitas Bhayangkara Jakarta Raya, 2023)
A large country like Indonesia should have a law on national security, as a basis for law enforcement and national security stability. Conflicts regarding the authority to take action against threats and enforce the law by the military and/or civilians should have been eliminated by formulating a comprehensive and firm terminology for National Security as a whole. The separation of laws and MPR Decrees regarding the TNI and POLRI clearly describes the duties and powers of each, including the handling and types of threats faced. The problem of